Use of Simulator Equipment for the Development and Testing of Vessel Control Systems - Zinchenko, Serhii; Mateichuk, Vadym; Nosov, Pavlo; Popovych, Ihor; Solovey, Oleksandr; Mamenko, Pavlo; Grosheva, Olga (Electrical, Control and Communication Engineering, 2020)
One of the ways to reduce human influence on the control process is the development of automated and automatic control systems. Modern control systems are quite complex and require preliminary ground testing. The article considers the issues of creating Imitation Modelling Stand for such control system synthesis and testing. For this reason, a Control System Model was integrated into the local computer network of the navigation simulator NTPRO 5000. The authors of the paper developed and tested software for information exchange between the navigation simulator and the Control System Model. The authors also developed a functional module of collision avoidance with many targets for testing in a closed loop system with virtual training objects. The results showed that the developed Imitation Modelling Stand allowed developing and testing functional modules of the control systems. In comparison with the found analogues, it is easy to include in a closed simulation cycle various models of command devices, actuators, control objects, objects of training scene, weather conditions; it is universal both for solving problems of manual control and for developing and testing automatic and automated control systems; it is not highly specialised and is created at minimal costs.